Exploiting yoeB‐yefM toxin‐antitoxin system of Streptococcus pneumoniae on the selective killing of miR‐21 overexpressing breast cancer cell line (MCF‐7). Issue 3 (20th September 2019) - Houri, Hamidreza; Ghalavand, Zohreh; Faghihloo, Ebrahim; Fallah, Fatemeh; Mohammadi‐Yeganeh, Samira
Abstract: Toxin‐antitoxin (TA) systems are two‐component genetic modules widespread in bacterial and archaeal genomes, in which the toxin module is rendered inactive under resting conditions by its antitoxin counterpart. Under stress conditions, however, the antitoxin is degraded, freeing the toxin to exert its lethal effects. Although not evolved to function in eukaryotes, some studies have established the lethal activity of these bacterial toxins by inducing apoptosis in mammalian cells, an effect that can be neutralized by its cognate antitoxin. Inspired by the way the toxin can become active in eukaryotes cells, we produced an engrained yoeB ‐ yefM TA system to selectively kill human breast cancer cells expressing a high level of miR‐21. Accordingly, we generated an engineered yefM antitoxin gene with eight miR‐21 target sites placed in its 3′untranslated region. The resulting TA system acts autonomously in human cells, distinguishing those that overexpress miR‐21, killed by YoeB, from those that do not, remaining protected by YefM. Thus, we indicated that microRNA‐control of the antitoxin protein of bacterial TA systems constitutes a novel strategy to enhance the selective killing of human cancer cells by the toxin module. The present study provides significant insights for developing novel anticancer strategies avoiding off‐target effects, a challenge that has been pursued by many investigators over the years. Abstract : The current study is of particular importance and could provide insights for developing novel anticancer therapeutic strategies avoiding off‐target effects using prokaryotic toxin‐antitoxin (TA) systems. This study is the first to explore the potent selective anticancer activities of a bacterial TA system based on tissue‐specific microRNA regulation.